Percep????o dos gestores de unidades b??sicas de sa??de com estrat??gia sa??de da fam??lia do munic??pio de S??o Paulo sobre a implanta????o do programa nacional de melhoria do acesso e da qualidade na aten????o b??sica (PMAQ-AB) - Chimara, Mar??lia Bezulle (2015)
The Ministry of Health launched the National Programme for Improving Access and Quality of Primary Care (PMAQ-AB) which aims to promote increased access and improved quality of primary care, with a quality standard comparable at national, regional and local levels. The objective of this study is to understand the perception of Basic Health Units managers with Health Strategy of S??o Paulo city's Family on the implementation of the National Program for Improving Access and Quality in Primary Care (PMAQ-AB). We used an exploratory, qualitative dealt with the method of case studies, from nine managers interviews in three Basic Health Units with the family health strategy on the east side of S??o Paulo. The collected data were analyzed by thematic analysis method. We observed that the perception of managers showed that the context for implementation of the evaluated units PMAQ was favorable since professionals were motivated, had clear understanding of the proposal and the objectives and there was a proper management to reduce resistance. The implementation process of PMAQ, however, was problematic, since there was no proper coordination between management and workers, the implementation was not considered continuous, engagement of the teams was partially satisfactory, the structural conditions, time and resources were not satisfactory in PMAQ deployment process. Regarding the analysis of the effectiveness of the process of self-evaluation of PMAQ was not considered an appropriate and useful tool for the planning of actions, yet managers say the PMAQ has reached the goal of improving quality in SUS, as well as the objectives improving access and effectiveness of actions.